Epidemiology and psychosocial assessment of COVID-19 among workersof the Nigeria Centre for Disease Control infected with COVID-19 - Fatima Saleh; David Idowu Olatunji; Ehichioya Ofeimun; Evaezi Okpokoro; Emily Crawford; Mahmood Dalhat; Ehimario Igumbor; Sunday Eziechina; Stella Inweregbu; Chinwe Lucia Ochu; Ihekweazu Chikwe (Journal of Public Health in Africa, 2023)
Background. COVID-19 is a global health crisis. By 2021, Nigeria had 230,000 cases. As the national public health institute, NCDC leads the COVID-19 response. Due to constant contact with infected patients, agency employees are at high-risk. Here, we describe the transmission and psychosocial effects of COVID-19 among infected NCDC workers as a learning curve for minimizing occupational transmission among frontline public health workers in future outbreaks.